PENGARUH PERBEDAAN PENGELOLAAN AGROEKOSISTEM TANAMAN TERHADAP STRUKTUR KOMUNITAS SERANGGA PADA PERTANAMAN KEDELAI DI NGALE, KABUPATEN NGAWI, JAWA TIMUR - Lutfi Afifah; Purnama Hidayat; Damayanti Buchori; Marwoto .; B T Rahardjo (Universitas Lampung, 2015)
Effect of different agroecosystem management on community structure of insects in soybean crop in Ngale, Ngawi District, East Java. Insect community structures in agroecosystem may always change. Agroecosystem management techniques affect insect community structure. The aim of this study was to determine the diversity and composition of insects on soybean plants under different pest management systems and varieties. The experiment design was split plot with varieties (Anjasmoro and Wilis) as the main plots and pest management systems (Integrated Pest Management (IPM), Non-Chemical Management (P-NK), Chemical Management (P-K), and Control) as the sub plots. There were ten insect sampling sessions for each plot. Samplings were done in June until September 2013 using pitfall traps, sticky traps, sweep net, and yellow pan traps. Statistically the results of experiment showed that varieties and pest management had no significant differences to the insects diversity. Herbivore and beneficial insect in soybean crop had differences composition between varieties Anjasmoro and Wilis. In both soybean Anjasmoro and Wilis varieties, herbivore populations tend to be higher in the control plots compared to the IPM plots. Abundance of decomposers, parasitoids, and predators tend to be higher in the control and P-NK plots which were without the use of synthetic insecticides compared to the IPM and P-K plots which were given the treatment of synthetic pesticides. This indicates that the use of pesticides causes decrease in the beneficial insect populations such as pollinator, parasitoids, and predators.